TO REVIEW THE DESCRIPTION IN THE SOURCES OF THE HISTORICAL AND GEOGRAPHICAL STATE OF UZGEN AT THE BEGINNING OF THE XX CENTURY - M.Makhmudov (EPRA International Journal of Multidisciplinary Research (IJMR), 2023)
The article highlights the historical and geographical position of the city of Uzgen in the Republic of Kyrgyzstan in various sources.